Animal venoms: a novel source of anti-Toxoplasma gondii drug candidates - Yang, Dongqian; Liu, Xiaohua; Li, Jing; Xie, Jing; Jiang, Liping (Frontiers in Pharmacology, 2023)
Toxoplasma gondii (T. gondii) is a nucleated intracellular parasitic protozoan with a broad host selectivity. It causes toxoplasmosis in immunocompromised or immunodeficient patients. The currently available treatments for toxoplasmosis have significant side effects as well as certain limitations, and the development of vaccines remains to be explored. Animal venoms are considered to be an important source of novel antimicrobial agents. Some peptides from animal venoms have amphipathic alpha-helix structures. They inhibit the growth of pathogens by targeting membranes to produce lethal pores and cause membrane rupture. Venom molecules generally possess immunomodulatory properties and play key roles in the suppression of pathogenic organisms. Here, we summarized literatures of the last 15 years on the interaction of animal venom peptides with T. gondii and attempt to explore the mechanisms of their interaction with parasites that involve membrane and organelle damage, immune response regulation and ion homeostasis. Finally, we analyzed some limitations of venom peptides for drug therapy and some insights into their development in future studies. It is hoped that more research will be stimulated to turn attention to the medical value of animal venoms in toxoplasmosis.